Robustness and weakness of the classical nonlinear model for circular cones at supersonic speed: New closed-forms solutions, Crossed regions, and a new theoretical lower boundary - Ferreyra, Ricardo Tomás (2013)
Fil: Ferreyra, Ricardo Tomás. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.